2013
DOI: 10.1038/nature12611
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory signalling to the Arp2/3 complex steers cell migration

Abstract: Cell migration requires the generation of branched actin networks that power the protrusion of the plasma membrane in lamellipodia. The actin-related proteins 2 and 3 (Arp2/3) complex is the molecular machine that nucleates these branched actin networks. This machine is activated at the leading edge of migrating cells by Wiskott-Aldrich syndrome protein (WASP)-family verprolin-homologous protein (WAVE, also known as SCAR). The WAVE complex is itself directly activated by the small GTPase Rac, which induces lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
241
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 217 publications
(279 citation statements)
references
References 46 publications
24
241
0
Order By: Relevance
“…There are many potential mechanisms behind this effect. Dictyostelium is a well-studied model for cell movement (Dang et al, 2013;Artemenko et al, 2014) and has been explored in a range of pharmacological studies for identifying chemical targets (Robery et al, 2013;Waheed et al, 2014;Lockley et al, 2015). Indeed, a large number of studies have identified changes in cell behavior (particularly in movement) caused by deletion of individual proteins (Chattwood et al, 2014;Fets et al, 2014;Wessels et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There are many potential mechanisms behind this effect. Dictyostelium is a well-studied model for cell movement (Dang et al, 2013;Artemenko et al, 2014) and has been explored in a range of pharmacological studies for identifying chemical targets (Robery et al, 2013;Waheed et al, 2014;Lockley et al, 2015). Indeed, a large number of studies have identified changes in cell behavior (particularly in movement) caused by deletion of individual proteins (Chattwood et al, 2014;Fets et al, 2014;Wessels et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to NPFs like WASP and cortactin, the A region is found in several inhibitors of Arp2/3 complex, including PICK1 (71), Gadkin (72), and Arpin (73). These proteins block branching nucleation by competing with WASP family proteins for binding to the complex.…”
Section: Dynamic Multivalent Contacts With Actin Filaments Can Explaimentioning
confidence: 99%
“…Subsequently, the post-fixed specimens were dehydrated using a graded series of ethanol and then transferred to a graded series of t-butyl alcohols (freezing point 25.4˚C), the t-butyl alcohol substituted specimens were freeze-dried at 15˚C and at high vacuum (23). The experimental specimens were sputter-coated with platinum and then observed using a scanning electron microscope (S-750; Hitachi, Ltd., Tokyo, Japan) operating at 20 kV (24).…”
Section: Rna Extraction and Reverse Transcription-polymerase Chain Rementioning
confidence: 99%